2018
DOI: 10.15171/jrip.2018.18
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of ferulic acid on gentamicininduced nephrotoxicity in a rat model; role of antioxidant effects

Abstract: The most common symptoms of nephrotoxicity include decreased glomerular filtration, increased creatinine, blood urea nitrogen, uric acid, alkaline phosphatase, and electrolyte changes. Ferulic acid is a natural compound with a phenolic group which is found mainly in citrus, rice and coffee. In numerous studies, many roles have been identified for this substance, including anticancer, nephroprotective, hepatoprotective and anti-inflammatory activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Oxidative stress is a harmful event that is responsible for development of a wide range of disease [14]. In fact, ROS induce tissue injury through DNA damage and oxidation of lipid and proteins [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is a harmful event that is responsible for development of a wide range of disease [14]. In fact, ROS induce tissue injury through DNA damage and oxidation of lipid and proteins [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…FeA‐mediated HO‐1 upregulation reappeared as a protective mechanism against cisplatin‐induced nephrotoxicity in rats . In another study in rats with gentamicin‐induced nephrotoxicity, FeA increased superoxide dismutase, glutathione peroxidase and catalase, and consequently reduced the nephrotoxicity of gentamicin . Finally, in a very recent study, FeA was shown to prevent lead‐induced testicular oxidative stress in rats via possibly inhibiting lipid peroxidation and enhancing antioxidant defense systems …”
Section: Mechanism Of Action Of Hydroxycinnamic Acids: Recent Advancesmentioning
confidence: 93%
“…169 In another study in rats with gentamicin-induced nephrotoxicity, FeA increased superoxide dismutase, glutathione peroxidase and catalase, and consequently reduced the nephrotoxicity of gentamicin. 170 Finally, in a very recent study, FeA was shown to prevent lead-induced testicular oxidative stress in rats via possibly inhibiting lipid peroxidation and enhancing antioxidant defense systems. 172 www.soci.org V Coman, DC Vodnar compared to lean individuals.…”
Section: Caffeic Acid: Recent Advancesmentioning
confidence: 97%
See 1 more Smart Citation
“…With medical advances, plant-based drugs and compounds are being increasingly used in the hope for finding better treatments. [8910111213141516]…”
Section: Introductionmentioning
confidence: 99%